EXAMINATION THE PROCESS OF LONGITUDINAL SOLID WOOD PROFILE MILLING. PART II: INFLUENCE OF THE REVOLUTION FREQUENCY AND FEED RATE ON THE ROUGHNESS OF THE TREATED SURFACES (Innovation in Woodworking Industry and Engineering design, 2026)
This article presents the results of experimental studies of longitudinal solid wood profile milling. In the present part II, the influence of the cutter rotational frequency and the feed rate on the roughness of the processed surfaces are tested. The studies were carried out in the labor-atory of „Cutting of wood and cutting tools“ to University of Forestry. For this purpose universal wood shaper machine, model FD-3 (Bulgaria), with bottom-mounted shaft and mechanical feed of material was used. The results obtained can be used as a basis for the formation of specific recommendations aimed at increasing the reliability of the machine and the accuracy and quality of the production.